2009
DOI: 10.1177/1461444809105346
|View full text |Cite
|
Sign up to set email alerts
|

As real as real? Macroeconomic behavior in a large-scale virtual world

Abstract: This article proposes an empirical test of whether aggregate economic behavior maps from the real to the virtual. Transaction data from a large commercial virtual world -the first such data set provided to outside researchers -is used to calculate metrics for production, consumption and money supply based on real-world definitions. Movements in these metrics over time were examined for consistency with common theories of macroeconomic change. The results indicated that virtual economic behavior follows real-wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 17 publications
1
82
0
2
Order By: Relevance
“…However, similar to results of this study, other gamblers considered that use of electronic cash leads people to spend more when gambling online than offline. Studies have found that users of virtual worlds tend to follow similar patterns of economic consumption and expenditure as in real-world situations (Castronova et al, 2009). Further research is required to understand why for some people, virtual worlds and currencies are not used in the same way as real money would be.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to results of this study, other gamblers considered that use of electronic cash leads people to spend more when gambling online than offline. Studies have found that users of virtual worlds tend to follow similar patterns of economic consumption and expenditure as in real-world situations (Castronova et al, 2009). Further research is required to understand why for some people, virtual worlds and currencies are not used in the same way as real money would be.…”
Section: Discussionmentioning
confidence: 99%
“…현실세계에서 범죄 조직이 존재하듯 게 임 내에도 존재하며, 현실세계와 유사한 형태의 경제 행위가 발생 한다 [2]. 온라인 게임의 인기가 많아짐 에 따라 게임 내에서 획득하거나 구매하기 힘든 아이 템은 희소성을 갖게 되었다 [1].…”
Section: 서 론unclassified
“…To use virtual worlds for social science research, it is necessary to validate the "mapping" of group behavior in virtual worlds to real-world analogs [2,8]; a topic of key importance is understanding how models of MMOG guild membership relate to group formation in the real world. A second question is whether these models generalize to guilds in a different MMOG setting.…”
Section: Related Workmentioning
confidence: 99%